Β-Hydroxy-β-methylbutyrate and its impact on skeletal muscle mass and physical function in clinical practice: a systematic review and meta-analysis. Issue 4 (15th April 2019) - Bear, Danielle E; Langan, Anne; Dimidi, Eirini; Wandrag, Liesl; Harridge, Stephen D R; Hart, Nicholas; Connolly, Bronwen; Whelan, Kevin
ABSTRACT: Background: Loss of skeletal muscle mass and muscle weakness are common in a variety of clinical conditions with both wasting and weakness associated with an impairment of physical function. β-Hydroxy-β-methylbutyrate (HMB) is a nutrition supplement that has been shown to favorably influence muscle protein turnover and thus potentially plays a role in ameliorating skeletal muscle wasting and weakness. Objectives: The aim of this study was to investigate the efficacy of HMB alone, or supplements containing HMB, on skeletal muscle mass and physical function in a variety of clinical conditions characterized by loss of skeletal muscle mass and weakness. Methods: A systematic review and meta-analysis of randomized controlled trials reporting outcomes of muscle mass, strength, and physical function was performed. Two reviewers independently performed screening, data extraction, and risk-of-bias assessment. Outcome data were synthesized through meta-analysis with the use of a random-effects model and data presented as standardized mean differences (SMDs). Results: Fifteen randomized controlled trials were included, involving 2137 patients. Meta-analysis revealed some evidence to support the effect of HMB alone, or supplements containing HMB, on increasing skeletal muscle mass (SMD = 0.25; 95% CI: –0.00, 0.50; z  = 1.93; P  = 0.05; I 2  = 58%) and strong evidence to support improving muscle strength (SMD = 0.31; 95% CI: 0.12, 0.50; z  = 3.25; P  = 0.001; I 2  = 0%). Effect sizes were small. No effect on bodyweight (SMD = 0.16; 95% CI: –0.08, 0.41; z  = 1.34; P  = 0.18; I 2  = 67%) or any other outcome was found. No study was considered to have low risk of bias in all categories. Conclusion: HMB, and supplements containing HMB, increased muscle mass and strength in a variety of clinical conditions, although the effect size was small. Given the bias associated with many of the included studies, further high-quality studies should be undertaken to enable interpretation and translation into clinical practice. The trial was registered on PROSPERO as CRD42017058517.